Improving experimental reproducibility through comprehensive research protocols - Ivana Novak (FEBS Open Bio)
With this “In the Limelight: Research Protocols” special issue, FEBS Open Bio aims to highlight the critical importance of publishing reproducible and detailed scientific protocols that can be broadly adopted by laboratories working in molecular and cellular life sciences. This collection includes four protocols focused on sample preparation for structural analysis of macromolecules using X‐ray crystallography, covering both in vitro and in vivo approaches. Two additional protocols demonstrate the use of cellular systems to screen the enzymatic activity of various proteins, with potential applications in high‐throughput screening. Another protocol provides a comprehensive guide for the preparation and analysis of selective autophagy flux in cultured cells using flow cytometry. Finally, the issue concludes with a protocol integrating classical behavioral tests with cognitive components to assess both physical and cognitive dimensions of frailty.